Inflammasome-Independent NALP3 Contributes to High-Salt Induced Endothelial Dysfunction - Fu, Hui; Chen, Ji-Kuai; Lu, Wen-Jie; Jiang, Yu-Jie; Wang, Yuan-Yuan; Li, Dong-Jie; Shen, Fu-Ming (Frontiers in Pharmacology, 2018)
Abstract Backgrounds and aims: Na+ is an important nutrient and its intake, mainly from salt (NaCl), is essential for normal physiological function. However, high salt intake may lead to vascular injury, independent of a rise in blood pressure (BP). Canonical NALP3 inflammasome activation is a caspase-1 medicated process, resulting in the secretion of IL-18 and IL-1β which lead to endothelial dysfunction. However, some researches uncovered a direct and inflammasome-independent role of NALP3 in renal injury. Thus, this study was designed to investigate the possible mechanisms of NALP3 in high salt induced endothelial dysfunction. Methods and results: Changes in endothelial function were measured by investigating mice (C57BL/6J, NALP3-/- and wild-type, WT) fed with normal salt diet (NSD) or high-salt diet (HSD) for 12W, and thoracic aortic rings from C57BL/6J mice cultured in high-salt medium. Changes of tube formation ability, intracellular reactive oxygen species (ROS), and NALP3 inflammasome expression were detected using mouse aortic endothelial cells (MAECs) cultured in high-salt medium. Consumption of HSD for 12W did not affect BP or body weight in C57BL/6J mice. Endothelium-dependent relaxation (EDR) decreased significantly in C57BL/6J mice fed with HSD for 12W, and in isolated thoracic aortic rings cultured in high-salt medium for 24 h. Results from the aortic ring assay also revealed that the angiogenic function of thoracic aortas was impaired by either consumption of HSD or exposure to high-salt medium. NALP3-/- mice fed with HSD showed a relatively mild decrease in EDR function when compared with WT mice. Tube length of thoracic aortic rings from NALP3-/- mice was longer than those from WT mice after receiving high-salt treatment. Inhibiting NALP3 with a NALP3 antagonist, small interfering (si) RNA experiments using si-NALP3, and decomposing ROS significantly improved tube formation ability in MAECs under high salt medium. NALP3 expression was increased in MAECs cultured with high salt treatment and inhibiting NALP3 reversed the down-regulation of p-eNOS induced by high salt in MAECs. . Conclusions: High salt intake impairs endothelial function, which is at least in part mediated by increasing NALP3 expression.